Graduate midwives' perception of their preparation and support in using evidence to advocate for women's choice: A Western Australian study - Hauck, Yvonne; Lewis, L.; Kuliukas, Lesley; Butt, J.; Wood, J. (Churchill Livingstone, 2015)
A retrospective cohort study was conducted with 83 midwives working across the Western Australian (WA) maternity sector who graduated from one WA University. We explored midwives' attitudes and utilisation of research and assertive communication in addition to perceptions of their educational preparation to advocate for women. The greatest opportunity for research exposure was working on a clinical audit (25.3%). No differences were found between graduate groups using the Edmonton Research Orientation subscales, although findings suggest a positive view towards research. Midwives were more likely to be assertive with their clinical colleagues than a midwifery manager or medical colleague when: expressing their opinions (P = <0.001); saying no (P = <0.001); allowing others to express their opinions (P = <0.001); and making suggestions to others (P = 0.025). A qualitative phase with 15 midwives explored concepts around advocating for women. Four themes emerged: ‘having the confidence to question’, ‘communication skills’, work environment’ and ‘knowing the woman and what she wants’. Findings suggest strategies are needed in their entry to practice preparation and ongoing professional development to facilitate research engagement. Using assertive behaviour to provide feedback to clinical colleagues warrants attention to enhance reflective practice. Building communication skills through observing positive role models and participating in role play was highlighted.